From Honor to Dignity: Criminal Libel, Press Freedom, and Racist Speech in Brazil and the United States (Vanderbilt e-Journal of Luso-Hispanic Studies, 2016)
Reports on violence against journalists in Brazil have captured the concern of international human rights organizations. This article discusses a case involving another such concern: the use of criminal defamation laws in Brazil to punish journalists for criticizing public officials. At the same time, Brazilian media sources regularly report on crimes of racism, which most often involve derogatory name-calling and hate speech. By examining the intersection of these apparently contradictory concerns, this article sheds new light on speech rights in Brazil and the United States and argues that a comparative perspective is crucial to contextualizing and harmonizing free speech and its limitations under modern democratic constitutions. By considering the infusion of traditional notions of honor and status with post-World War II views of dignity, this article argues for a comparative consideration of how best to combat racism and whether hate speech regulation in the U.S. should be reconsidered. As such, the type of law often used to protect the powerful in Brazil could come to be used to protect the vulnerable in the United States and opens the possibility that the irony of free speech could become more than just a scholarly debate.